Religious value as the main influencing factor to customers patronizing Islamic bank - Idris, Asma' Rashidah; Nik Muhammad Naziman, Khadijah; Januri, Siti Sarah; Abu Hassan Asari, Fadli Fizari; Muhammad, Norrini; Md Sabri, Sabiroh; Jusoff, Kamaruzaman (IDOSI Publications, 2011)
Islamic bank in Malaysia was established in 1983. The development of the Islamic bank is increasingly challenging with the participation of more conventional banks offering banking products and services based on Islamic principles. This paper analyses the factors considered as important by academicians in public institutions of higher learning in selecting a particular bank. A sample of 250 Islamic bank customers in seven Malaysian Public Institutions of Higher Learning in the East Coast of Peninsular Malaysia was surveyed. The study revealed that religious value appears to be the most important factor. Other factors perceived to be important include ATM services, financial security, cost and benefit and attractiveness. It is to be concluded that, even though there are a lot of determining factors the religious value practised by the consumers plays a vital role in influencing them to patronize Islamic banking. For future studies, it is recommended to add more samples from other categories of consumers from different parts of the country.